2014
DOI: 10.1002/bjs.9491
|View full text |Cite
|
Sign up to set email alerts
|

Validation of international consensus guidelines for the resection of branch duct-type intraductal papillary mucinous neoplasms

Abstract: The new consensus guidelines provide better sensitivity, performance of factors predicting malignancy, and balanced accuracy in the diagnosis of BD-IPMN malignancy. Size alone was limited in predicting malignancy. Variability in clinical significance of the individual factors associated with a risk of malignancy indicates the need for a tailored approach in the management of patients with BD-IPMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 20 publications
5
97
2
2
Order By: Relevance
“…Based on their results, cyst size was not even related with malignant progression. Similarly, a recent study (92) that also analyzed a BD-IPMN surgical cohort showed the presence of mural nodules and MD dilation as the best predictors of malignancy. Cyst size greater than 3 cm seems to be the most debatable risk factor with some studies (93) supporting its role as an independent predictor of malignancy and other publications (44) recommending a conservative approach with close surveillance if present alone without other "worrisome features".…”
Section: Current Guidelines and Recommendationsmentioning
confidence: 67%
“…Based on their results, cyst size was not even related with malignant progression. Similarly, a recent study (92) that also analyzed a BD-IPMN surgical cohort showed the presence of mural nodules and MD dilation as the best predictors of malignancy. Cyst size greater than 3 cm seems to be the most debatable risk factor with some studies (93) supporting its role as an independent predictor of malignancy and other publications (44) recommending a conservative approach with close surveillance if present alone without other "worrisome features".…”
Section: Current Guidelines and Recommendationsmentioning
confidence: 67%
“…1). Of these studies, 33 investigated mural nodules5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 21 examined dilatation of the main pancreatic duct (MPD)7 9, 15 16, 18 21, 23 26, 27 30, 32 36, 38, 39, 40, 41, 42, 43, 44, 45, 46, 21 analysed cyst size5 7, 8, 9 14, 15 18, 20 23, 25 27, 28 31, 36 38, 40 41, 43 47, 48, 49, 17 assessed CA19‐9 increase…”
Section: Resultsmentioning
confidence: 99%
“…15 Many studies have distinguished the imaging findings of malignant BDIPMNs. 8,13,16,17 In contrast, few studies of the imaging findings of malignant MD-IPMNs have been published 14,18,19 because surgical resection has been recommended for all MD-IPMNs. However, recent studies suggested nonoperative management of MD-IPMNs in selected patients with lower risk because the natural history of MDIPMNs can be variable.…”
mentioning
confidence: 87%